2019
DOI: 10.3390/biom9110695
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Mechanism of Utilizing Corn Steep Liquor as the Sole Nitrogen Resource for Lipid and DHA Biosynthesis in Marine Oleaginous Protist Aurantiochytrium sp.

Abstract: In the current study, corn steep liquor (CSL) is evaluated as an ideal raw agro-material for efficient lipid and docosahexaenoic acid DHA production by Aurantiochytrium sp. Low CSL level in medium (nitrogen deficiency) stimulated the biosynthesis of lipids and DHA while inhibiting cellular growth. The transcriptomic profiles of the Aurantiochytrium sp. cells are analyzed and compared when cultured under high (H group), normal (N group), and low (L group) levels of CSL in the medium. The discriminated transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…For S. sp. HBW10, the relative content of PUFAs in the total fatty acids was obviously less than in the thraustochytrid strains previously isolated from the tropical and subtropical areas of China as we reported previously, not to mention the cold habitats [6]. Thraustochytrid strains isolated from a low-temperature environment had been speculated to produce more PUFAs, which had been proved by our previous study [27], as well as those reported elsewhere [41][42][43].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…For S. sp. HBW10, the relative content of PUFAs in the total fatty acids was obviously less than in the thraustochytrid strains previously isolated from the tropical and subtropical areas of China as we reported previously, not to mention the cold habitats [6]. Thraustochytrid strains isolated from a low-temperature environment had been speculated to produce more PUFAs, which had been proved by our previous study [27], as well as those reported elsewhere [41][42][43].…”
Section: Discussionsupporting
confidence: 72%
“…This might be explained by the phytoplankton bloom which triggered periodic explosive growth of thraustochytrids, a kind of saprophytic protist. Antibiotics were added into the isolation and purification medium for bacteria and fungi elimination as mentioned previously [6]. Notably, more antibacterial drugs were needed for strain isolation of thraustochytrids in temperate habitats than that in tropical waters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al found that a low-concentration corn steep liquor solution facilitated the docosahexaenoic acid production of thraustochytrids , and high-concentration of corn steep liquor led to increased biomass. The transcriptomic analysis was performed at high, normal, and low levels of corn steep liquor in culture medium to elucidate the low level of corn steep liquor affecting the perception and transduction of a limited-nitrogen signal and interactions between the transcription factors at the transcriptional level for improving lipid and docosahexaenoic acid productivity, providing new directions for subsequent optimization of production (Wang et al 2019 ). The contents of total lipids and exopolysaccharides in P. purpureum were significantly improved under nitrogen stress.…”
Section: Applications Of Omics Technologies In the Process Optimizati...mentioning
confidence: 99%
“…Acetogenesis and methanogenesis are slower processes that produce methane [ 9 , 10 ]. Anaerobic digestion has appeared to be one of the most reliable processes with a broad future potential [ 11 ]. Anaerobic digestion comprises sequential processes accomplished by microorganisms that break down biodegradable material in the absence of oxygen [ 12 ].…”
Section: Introductionmentioning
confidence: 99%